Analisis Postur Kerja Pada Proses Pembuatan Besi Baja Bagian Drilling Dengan Metode Rula dan Reba di PT. RAVANA JAYA - Danindra Dwi Maulana; Hidayat Hidayat; Efta Dhartikasari Priyana (G-Tech: Jurnal Teknologi Terapan, 2025)
PT. Ravana Jaya is a general contractor working on steel fabrication and has several partners from small, medium, and large scale companies. Observations showed that workers reported complaints related to pain in several parts of the body in the upper neck, lower neck, back, and left and right shoulders with a percentage value of 85% in the location of pain complaints in the upper neck area. This research uses the RULA (Rapid Upper Limb Assessment) and REBA (Rapid Entire Body Assessment) methods. The results of the RULA and REBA scores in the punching process are 7 and 9 with a high risk category so that it is necessary to hold a work posture improvement solution by adjusting the height of the workstation and using an adjustable bench, using ergonomic tools such as drilling machines and material support tools to reduce physical loads, job rotation and regular breaks to prevent muscle fatigue. These improvements are not only beneficial for the health and well-being of workers, but also for the sustainability of company operations.